Peningkatan Kemampuan Menulis Karangan Narasi dengan Media Gambar Serial: (Penelitian Tindakan Kelas di SDN 1 Tegal Ombo, Lampung Timur) - Widodo, Suyud; Sugianto, Bambang Eko; Aditya, Dimas Bagus (STKIP PGRI Bandar Lampung, 2024)
This classroom action research (CAR) was conducted on students at SD Tegal Ombo Way Bungur, East Lampung, school year 2024/2025. This research refers to the Kemmis and McTaggart model, with the aim of improving the ability to write narrative essays through the use of serial image media. The research was carried out in three cycles, in which each cycle consisting of planning, implementation, observation and reflection stages. Data were collected through observation, interviews and writing tests. The results of the research show firstly that there is an increase in the learning process of writing narrative essays using serial image media, either in terms of motivation, interest, creativity and writing structure. Second, there was an increase in the results of the ability to write narrative essays, starting from the final test of the first cycle to the end of the third cycle. As in the first cycle test results the average score was 30.90 (low level ability), in the second cycle test the average score was 48.73 (medium level ability), and the third cycle test increased to 74.55 (high level ability). Thus, the use of serial image media has proven to be effective in improving students' ability to write narrative essays, and is recommended for application in Indonesian language learning in other classes.